2013
DOI: 10.1186/bcr3408
|View full text |Cite
|
Sign up to set email alerts
|

The estrogen-regulated anterior gradient 2 (AGR2) protein in breast cancer: a potential drug target and biomarker

Abstract: Initially discovered as an estrogen-responsive gene in breast cancer cell lines, anterior gradient 2 (AGR2) is a developmentally regulated gene belonging to the protein disulfide isomerase (PDI) gene family. Developmentally, AGR2 is expressed in the mammary gland in an estrogen-dependent manner, and AGR2 knockout and overexpression mouse models indicate that the gene promotes lobuloalveolar development by stimulating cell proliferation. Although AGR2 overexpression alone seems insufficient for breast tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 72 publications
3
100
0
1
Order By: Relevance
“…We also observed significant upregulation of other genes in CSFTCs, such as AGR2 (log 10 RQ ÂŒ 3.53; adj P ÂŒ 0.0007), TFF3 (log 10 RQ ÂŒ 3.21; adj P ÂŒ 0.0007), and GRB7 (log 10 RQ ÂŒ 2.86; adj P ÂŒ 0.01; Supplementary Table S3). Overexpression of these genes has been correlated with aggressive cancer biology (20)(21)(22)(23). Although statistical significance was not achieved, MYC (log 10 RQ ÂŒ 0.85) was upregulated in CSFTCs as compared with leukocytes (Supplementary Table S3).…”
Section: Gene Expression Profilingmentioning
confidence: 99%
“…We also observed significant upregulation of other genes in CSFTCs, such as AGR2 (log 10 RQ ÂŒ 3.53; adj P ÂŒ 0.0007), TFF3 (log 10 RQ ÂŒ 3.21; adj P ÂŒ 0.0007), and GRB7 (log 10 RQ ÂŒ 2.86; adj P ÂŒ 0.01; Supplementary Table S3). Overexpression of these genes has been correlated with aggressive cancer biology (20)(21)(22)(23). Although statistical significance was not achieved, MYC (log 10 RQ ÂŒ 0.85) was upregulated in CSFTCs as compared with leukocytes (Supplementary Table S3).…”
Section: Gene Expression Profilingmentioning
confidence: 99%
“…Since AGR2 is reportedly up-regulated in various types of cancers, its utility as a cancer biomarker and therapeutic target has been investigated by numerous researchers (Brychtova et al 2011;Chevet et al 2013;Salmans et al 2013). Lepreux et al (2011) reported that AGR2 expression was high in normal columnar cholangiocytes and that its expression pattern appeared to be conserved during cholangiocarcinoma development.…”
Section: Introductionmentioning
confidence: 99%
“…It has been discovered to be overexpressed in many adenocarcinomas. Recent clinical studies have identified AGR2 protein as a potential biomarker of multiple cancers, including breast, prostate, ovarian, intestinal and colon cancers [2][3][4][5][6][7][8][9][10]. Although a number of researchers have developed various AGR2 detection methods in cancers, quantitative analysis is rarely reported and remained more studies for early diagnosis and treatment [11][12][13].…”
Section: Introductionmentioning
confidence: 98%